Where Are We? Finding a Canadian Curriculum - Sameshima, Pauline; Lee, Carol; Tsun Haggarty, Holly (Journal of the Canadian Association for Curriculum Studies, 2025)
This issue defines a Canadian curriculum amid political pressures and colonial legacies, emphasizing ongoing relational and experiential processes that foreground equity, diversity, inclusion and decolonization. Rather than treating curriculum as static content, contributors emphasize curriculum-as-encounter—approaching curriculum in ways that value ethical relationships, sustained engagement with colonial histories and the integration of Indigenous ways of knowing. Authors in this issue advocate for the unsettling of normalized settler colonial structures, and they invite new ways of living together in Canada. By upholding ethical responsibility, place and people, this issue advances a complex vision for Canadian curriculum rooted in reconciliation and authentic engagement.